Improving students’ digital literacy in biology learning through a RICOSRE-based digital module - Ilzha Akbar Muharomi Wicaksono; Susriyati Mahanal; Frida Kunti Setiowati (Universitas Papua, 2026)
Digital literacy is essential in biology learning as students increasingly use digital sources to access scientific information. However, many students still struggle to evaluate online information, while digital platforms often emphasize content delivery rather than digital literacy development. This study examined the effectiveness of a Google Sites-based digital module integrated with RICOSRE in improving students’ digital literacy. This study employed a quasi-experimental method by comparing two intact groups through pretest and posttest procedures. The participants involved 70 students: 34 in the experimental group and 36 in the control group. Data were collected through a test instrument that had been validated and developed with reference to Greenstein’s framework, covering information finding, use of multiple sources, information selection, information evaluation, source and message consideration, and production of original work. Data were analyzed using ANCOVA, N-gain, and effect size. The analysis revealed a significant difference in digital literacy scores, with the experimental group outperforming the control group after controlling for pretest scores, F = 128.008, p < 0.001, partial η² = 0.656. The N-gain score was also higher in the experimental group, 0.57 versus 0.28. These findings indicate that the module effectively strengthens students’ digital literacy in biology learning.